Pulmonary Embolism: Diagnosis and Treatment - Piasek, Ewa; Padała, Olga; Krupa, Adrianna; Putowski, Maciej; Konopelko, Michał (Journal of Education, Health and Sport, 2019)
Pulmonary embolism is occlusion of one or more pulmonary artery . Deep vein thrombosis is responsible for most cases of PE. Pulmonary embolism is in 50% cases asymptomatic. Risk factors are: surgery, trauma, venous catethers, superficial vein thrombosis, immobilization, obesity, policythemia vera, infection, cancer, hormonal contraceptives. The aim of this paper is to present available diagnostic tools and treatment method of pulmonary embolism. Nowadays, there are many tools, such as ECG, laboratory markers or imaging technique, which help us in diagnosis of pulmonary embolism. They consist of: ECG, laboratory markers and imaging techniques. D-dimer are standard laboratory test in diagnosis of PE. D-dimer has high diagnostic sensivity and is usually used to exlude PE. Ultrasonography is also useful for detection of PE. Ultrasound is non-invasive technique, which can be performed by the bed or during surgery. More advanced techniques of imaging, such as ventilation-perfusion scan or computed tomography pulmonary angiogram (CPTA) are also used in diagnosis of pulmonary embolism. Method of treatment depends on patients state and comorbidities: anticoagulation, thrombolysis, surgical embolectomy and cathether-directed thrombolysis, Pulmonary embolism is often diagnosis of exclusion. Nowadays, with development of imaging techniques and laboratory tests, diagnosis of PE and proper treatment may be implemented quickly.